THE INTERACTION OF STAGES IN THE DEVELOPMENT OF UZBEK MINIATURE. THE INTERPRETATION AND EXTIRPATION OF TODAY’S NEW UZBEK MINIATURE - Mamadjonova, Shahlo Toʻychiboy qizi (Educational Research in Universal Sciences, 2023)
the article covers the interpretation of Uzbek miniature art and aspects of this miraculous art that are distinguished in nobility within the renewing arts.Stages in the development of miniature are of course important, in which the emphasis is mainly on the fact that they can also draw attention to the issues of hos and change to periods, and it should not be exaggerated to say that it was paid.